TI_GERICHTE 12.2004.217 vom 13. Dezember 2005 , compravendita e appalto - difetti - minor valore dell'opera - opere supplementari - TI Tribunale d'appello (2005)
compravendita e appalto - difetti - minor valore dell'opera - opere supplementari